Monitoring of Chemical Species in Soils, Waters and Plants near the Active Copper Mine Tailing Dam Ovejeria (Central Chile) - Diaz-Schulze, O; Pastene-Olivares, R; Pastene-Olivares, R (Institute for Ionics, 2024)
Chile, the world’s largest copper producer, generates massive amounts of mine tailings that are a source of ongoing environmental concern for local communities. The main objective of this work is to evaluate the concentration of As, Cd, Cr, Cu, Fe, Mn, Mo, Ni, Pb, Zn and SO42− in soils, water and vegetation in the communities surrounding the Cu Ovejería mine tailings dam, in central Chile. Soils, water and plants samples were collected from the towns of Chacabuco, Huechún, Huertos Familiares, Punta Peuco and Santa Matilde, which are located at 3 to 8 km from the mine tailings site, operated by CODELCO since 1999. The results showed that the levels of metals/metalloids and SO42− in water (pH 6.7–7.9) met both WHO limits and Chilean water quality standards for multiples uses. In soil (pH 7.7–8.4), total and available concentrations of metals/metalloids did not exceed international reference values. Plants with acceptable levels of metals and S were Citrus limon, Eucalyptus, Schinus molle, Prunus persica, Medicago sativa, Citrus sinensis and Ficus carica. The only species with Fe content well above the reference value and with high concentrations of other metals (Cu, Mn, Mo and Pb) was Acacia caven. The concentrations of chemical species determined between 2015 and 2018, in different media and locations near the active Cu tailings dam Ovejeria, in central Chile, allow to conclude that in general the levels are comparable to national and international references and do not indicate contamination. © The Author(s), under exclusive licence to Springer Nature Switzerland AG 2024.